Proceedings of International Conference on Aerospace System Science and Engineering 2018 - Jing, Zhongliang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents high-quality contributions in the subject area of Aerospace System Science and Engineering, including topics such as: Trans-space vehicle systems design and integration, Air vehicle systems, Space vehicle systems, Near-space vehicle systems, Opto-electronic system, Aerospace robotics and unmanned system, Aerospace robotics and unmanned system, Communication, navigation and surveillance, Dynamics and control, Intelligent sensing and Information fusion, Aerodynamics and aircraft design, Aerospace propulsion, Avionics system, Air traffic management, Earth observation, Deep space exploration, Bionic micro-aircraft/spacecraft. The book is a selection of articles from the 2nd International Conference on Aerospace System Science and Engineering, held in Moscow, Russia, from 31 July to 1 August 2018. The conference is co-organized by Shanghai Jiao Tong University and Moscow Aviation Institute. This is a forum that brings together experts in astronautics andaeronautics to share new ideas and findings.
Remote Sensing Image Registration Based on the HEIV Model -- Dynamics of Miura Folded Metamaterials -- Automatic Power Line Detection for Low-Altitude Aircraft Safety Based on Deep Learning -- A Survey on Object Tracking in Aerial Surveillance -- Application and improvement of gas turbine blades film cooling.
Keywords: Aerospace engineering; Astronautics; Telecommunication; Solar system; Control engineering; Aerospace Technology and Astronautics; Communications Engineering, Networks; Space Physics; Control and Systems Theory